Transcendental Philosophy and Post-Neo-Kantianism. On the Continuity of the Problem History of Transcendental Systematics in the 20th Century - Boch, Michael (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Filosofii͡a, 2024)
This article aims to make a contribution to the problematic history of the transcendental philosophical tradition up to the present day. At the centre is the question of the continuity of transcendental philosophical research in the 20th century with regard to the situation before and after the Second World War. The decisive point of reference here is Neo-Kantianism. Canonical Neo-Kantianism research defines it on the basis of its core phase between 1895 and 1912, which it precedes with an emergence and ends with a dissolution. There is no consensus among researchers when it comes to determining and dating the emergence and end of Neo-Kantianism. However, the majority of researchers agree that the end of Neo-Kantianism was between 1918 and 1945, marking a break in this philosophical tradition. Nevertheless, there is also a research perspective that allows a post-history to follow the core phase of Neo-Kantianism. However, the term Neo-Neo-Kantianism proposed for this is rejected by the majority of research in Neo-Kantianism. Kurt Walter Zeidler and Andrej Noras have taken up research into the post-history of Neo-Kantianism in different ways. On the one hand, Zeidler makes “Post-Neo-Kantian systematics” the guiding principle of his analysis with a view to continuity within the Neo-Kantian school of realist criticism. Andrej Noras, on the other hand, interprets the ontological interpretation of Kant in the 1920s and its critique of epistemologically orientated classical Neo-Kantianism as Post-Neo-Kantianism, which he follows with Neo-Neo-Kantianism as a critique of the critique of Post-Neo-Kantianism. The two authors thus argue in favour of a continuity of the transcendental philosophical tradition in the 20th century, whereby they make the supposed end of neo-Kantianism the starting point of their investigations. In this article, the terms Neo-Kantianism, Neo-Neo-Kantianism and Post-Neo-Kantianism will be clarified and contextualised within Neo-Kantian research. On the basis of this presentation, a perspective for the transcendental philosophical systematics of the 21st century will then be developed, which productively appropriates the 20th century as its problem-historical foundation.